1997
DOI: 10.1152/ajpregu.1997.273.1.r324
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in the pressor effects of hepatic portal venous fatty acid infusion

Abstract: Portal venous infusion of oleate solution has pressor effects. We have examined efferent mechanisms, measured the response to sustained infusion, and determined the effect of linoleate. Eight conscious animals received concurrent infusions of prazosin or vehicle with portal venous infusion of oleate. Oleate alone increased mean arterial pressure from 109.0 +/- 4.1 to 123.0 +/- 5.8 mmHg (P = 0.02), whereas no increase in blood pressure occurred when oleate was infused with prazosin. In 10 rats, concurrent infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 0 publications
5
42
1
3
Order By: Relevance
“…In the above-mentioned study from Grekin et al, 20 the increase in BP following portal oleic acid infusion was blunted from prazosin, an a 1 -adrenergic antagonist, but not from an angiotensin II receptor inhibitor, findings indicating the involvement of an a 1 -adrenergic mechanism in this BP elevation (Figure 1). These observations in favour of an a 1 -adrenergic-mediated action of NEFAs are in agreement with previous findings from Egan et al in humans.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 77%
See 1 more Smart Citation
“…In the above-mentioned study from Grekin et al, 20 the increase in BP following portal oleic acid infusion was blunted from prazosin, an a 1 -adrenergic antagonist, but not from an angiotensin II receptor inhibitor, findings indicating the involvement of an a 1 -adrenergic mechanism in this BP elevation (Figure 1). These observations in favour of an a 1 -adrenergic-mediated action of NEFAs are in agreement with previous findings from Egan et al in humans.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 77%
“…In another study of the same group, acute and chronic portal infusions of oleic acid, as well as acute infusion of linoleic acid were again associated with significant increases in BP. 20 Previous human studies provided indirect evidence in favour of an association between NEFA and the development of hypertension. Egan et al 21 observed that baseline plasma levels and turnover rate of NEFAs were increased in obese compared to lean individuals, but similar between obese hypertensive and obese normotensive subjects.…”
Section: The Effect Of Nefas On Bp Levelsmentioning
confidence: 99%
“…An infusion of FFAs results in elevated blood pressure in both animals and humans [36][37][38][39][40][41][42][43] . A large-scale population study concluded that the elevation of FFAs in human individuals is a highly significant risk factor for the subsequent development of hypertension [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Grekin et al (36) found that acute infusion of free fatty acids into the portal or systemic veins increased blood pressure and heart rate in rats, and that these effects were abolished by adrenergic blockade. Since portal vein infusion caused a greater rise in blood pressure than systemic iv infusion, afferent pathways originating in the liver were postulated to activate the sympathetic nervous system in response to increased levels of fatty acids (36).…”
Section: Do High Levels Of Fatty Acids Contribute To Increased Renal mentioning
confidence: 99%